Quantifying the pore structure of different biochars and their impacts on the water retention properties of Sphagnum moss growing media. (March 2020) - Turunen, Mika; Hyväluoma, Jari; Heikkinen, Jaakko; Keskinen, Riikka; Kaseva, Janne; Hannula, Markus; Rasa, Kimmo
Abstract : Amending growing media with biochar has the potential to sequester carbon and enhance the properties of the receiving substance. However, knowledge of the mechanisms of how biochar amends the physical properties of the material is incomplete. By combining 3D image analysis and more conventional methods, this study aimed to (1) characterise the pore structure properties of three different plant-based biochars and (2) quantify their impact on Sphagnum moss growing media physical properties. The 3D imaging showed that irrespective of the feedstock, the majority (0.80–0.94 m 3  m −3 ) of the biochar pore volume resided in pores with diameters 2–11 μm. Biochar pore properties shared similarities due to the structure of plant tissue. The application of biochar increased the water retention of the growing media by a maximum increase of 0.06 m 3  m −3 in the pore diameter range 1–8 μm. This is relevant for plant-available water and microbiological activity, which indicates the usability of the biochar amendments. From methodological point of view, the benefits of combining 3D imaging with conventional measurements and impacts of the water table continuum discontinuity between the biochar and the surrounding growing media were demonstrated. The design of biochar for optimal water retention would benefit from further studies quantifying pore structure characteristics of biochar produced from a wide range of feedstocks. Highlights: 3D image analyses of biochar showed pore diameters 2–11 μm dominated pore space. Plant tissue structure controlled the pore structure of biochars. Biochar affected moss moisture in regions relevant to plant-available water. Biochar partly acted as an isolated unit lacking contact with adjacent growing media. Quantifying biochar structure was needed to understand its water retention impacts.